DEVELOPMENT AND VALIDATION FOR NEW ANALYTICAL METHOD OF TIZANIDINE BY RP-HPLC - Sujita Kumari, Obed Singh (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
A new HPLC method development and validation for the analysis of Tizanidine in bulk and pharmaceutical formulation was developed and validated. The method was validated according to ICH validation parameters like accuracy, linearity, precision, robustness. The UV spectra for the standard solution was scanned in the wavelength of 200nm to 400nm. The iso-bestic point was determined at 318nm. Peak of Tizanidine was resolved with the Mobile phase of 50:50 v/v of water and methanol and by adjusting the pH to 4.0 with ortho-phosphoric acid or sodium hydroxide and the satisfactory result in term of retention time, peak area, symmetry was obtained. All the analysis parameters were carried out using Shimadzu C18 column (15cm×4.6mm internal diameter, 5µ particle size) and the peak of Tizanidine showed well resolved at wavelength of 318 nm. The retention time of Tizanidine was found to be 5.574minute at the flow rate of 1.0 ml per minute and at 20µl of sample. The regression coefficient(r2) was found to be 0.99972 for standard solution and 0.99964 for test solution, which is within the acceptance criteria. The percentage recovery of assay was 99.36% to 100.59%.